Implementation of EU Readmission Agreements : Identity Determination Dilemmas and the Blurring of Rights - Carrera, Sergio (SpringerBriefs in law,, 2016)
By examining the implementation dynamics of EU Readmission Agreements (EURAs), this book addresses the practical reasons why irregular immigrants cannot be expelled. EURAs are one of the vital legal instruments framing EU external migration law with regard to the expulsion of irregular immigrants, yet their implementation has met with various obstacles. Above all, the process of determining an individual's legal identity has proven to be one of the most controversial aspects in the implementation of EURAs. The analysis shows that the process of identifying who is whose national in the context of readmission creates two existential dilemmas: first from the perspective of the sovereignty of third countries of origin and the legal standards laid out in international instruments as regards states' powers in determining nationality, and second regarding the agency of the individual as a holder of fundamental human rights. How do the EURAs deal with or aim at alleviating these identity determination dilemmas? The book provides a comparative analysis of the administrative procedures and rules envisaged by EURAs aimed at proving or presuming the nationality of the persons to be readmitted to their country of origin. It focuses on the ways in which nationality is to be determined or presumed in the scope of the 2010 EURA with Pakistan, and compares it with those foreseen in the EURAs with Armenia, Azerbaijan, Cape Verde, Georgia, and Turkey. As such, the book provides a unique and up-to-date study of EURAs and their implementation challenges in the broader context of EU external migration law and policy.--